Congenital Heart Diseases: Recent Insights into Epigenetic Mechanisms - José Manuel Rodríguez-Pérez; Diego B. Ortega-Zhindón; Clara Villamil-Castañeda; Javier Santiago Lara-Ortiz; Verónica Marusa Borgonio-Cuadra; Jorge L. Cervantes-Salazar; Juan Calderón-Colmenero; Zeomara Nathali Escalante-Ruiz; Eduardo Retama-Méndez; Yessica C. Hernández-García; Nonanzit Pérez-Hernández (Cells)
Congenital Heart Diseases (CHDs) are a heterogeneous group of structural abnormalities affecting the heart and major arteries, which are present in at least 1% of births worldwide. Studies have linked CHD to both genetic and environmental factors. In this regard, it has been demonstrated that changes in the epigenetic pattern impact the expression of key genes involved in proper cardiac development. Therefore, it is suggested that aberrant epigenetic mechanisms may contribute to the development of these pathologies. Here, we review and summarize the main epigenetic mechanisms involved in CHD. Moreover, cardiac development and the importance of the environment and CHD are also addressed.